Antioxidant Activity Test of the Ethyl Acetate Fraction of Beluntas Leaves (Pluchea indica L.) in White Male Rats Wistar Strain Induced Carbon Tetra Chloride - Fitrya; Vitri Agustiarini; Adelia Indriyan; Herlina; Dwi Hardestyariki; Eka Febri Zulissetiana (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
Beluntas leaves contain flavonoids which have antioxidant effects. The purpose of this research was to determine the flavonoid total content, the effect of ethyl acetate fraction of beluntas on Malondialdehyde (MDA) levels, catalase enzyme activity, macroscopic pathology, histopathology description of white male rats wistar strain induced by CCl4 and of determining the best dose antioxidant. In this study, the in vivo tests used TBARS methods which consisted of six groups that are normal control, positive control (vitamin C 10 mg/kgBW), negative control (Na-CMC 1%), and treatment groups were given ethyl acetate fraction of beluntas leaves at doses 25 mg/kgBW, 50 mg/kgBW and 100 mg/kgBW. The total flavonoid content of the ethyl acetate fraction of beluntas leaves was 153 mgQE/g. The average results of MDA levels normal, positive, negative, doses fraction groups of 25, 50, and 100 mg/kgBW, respectively, were 1.155; 0.471; 1.892; 1.218; 0.826 and 0.512 nmol/mL. The average results of catalase enzyme activity of normal, positive, negative, doses fraction groups 25, 50, and 100 mg/kgBW, respectively, were 22.131; 40.489; 3.103; 14.145; 32.176, and 39.814 U/mL. The macroscopic and histopathology results show an improvement after being given the ethyl acetate fraction of beluntas leaves at doses of 25, 50, and 100 mg/kgBW compared to the negative control. The results showed that the ethyl acetate fraction of beluntas leaves reduce MDA levels and increases catalase enzyme activity. Ethyl acetate fraction of beluntas leaves at 100 mg/kgBW had the most potent antioxidant activity compared to doses of 25 and 50 mg/kgBB which were shown by Duncan’s statistical analysis that there was no significant difference with positive control.